Carbon dioxide capture characteristics from flue gas using aqueous 2-amino-2-methyl-1-propanol (AMP) and monoethanolamine (MEA) solutions in packed bed absorption and regeneration columns. (January 2015) - Khan, Anoar Ali; Halder, G.N.; Saha, A.K.
Highlights: Experiments were performed in mini pilot plant using flue gas generated from a coal fire boiler. Packed bed absorption was modelled and CO2 capturing characteristics were compared for AMP and MEA. CO2 removal efficiency using MEA and AMP were 99.13 and 98.88%, respectively. Regeneration of AMP was 41.7% less energy intensive than MEA. Experimental absorption data plotted with response surface methodology fitted data shows a good agreement. Abstract: Increasing concentration of CO2 in the atmosphere contributing potential negative impact to the environment has been the subject of worldwide attention over the past few decades. CO2, one of the main greenhouse gases (GHG) is getting emitted to the environment from different industries such as fossil fuelled power plants, cement industry, refinery and synthetic ammonia production units etc. Gas scrubbing using aqueous alkanolamine solutions is the most promising retrofit option for post combustion carbon dioxide capture in recent days. The present study investigates an effective means of eliminating CO2 from flue gas using two primary amines, namely conventional monoethanolamine (MEA) and a sterically hindered amine, 2-amino-2-methyl-1-propanol (AMP). The CO2 absorption characteristics were experimentally examined in a packed column under various process conditions viz. CO2 partial pressure, gas and liquid flow rates, solvent concentrations and operating temperature and pressure. While the regeneration of solvent was studied at the temperature range from 368 to 382 K. The present work reports mainly a comparative study of absorption and regeneration behaviour of the two alkanolamines which necessarily include the specific rate of absorption, percentage of CO2 absorbed, CO2 loading during absorption and residual CO2 after solvent regeneration and regeneration efficiency. The specific rate of absorption of AMP and MEA are observed to be (2.11–4.03) × 10 −5 kmol/m 2 s and (5.36–9.55) × 10 −5 kmol/m 2 s, respectively. The maximum percentage of CO2 absorbed using MEA is 99.13% and AMP is 98.88%. In case of solvent loading capacity (moles of CO2 per mole of amine) AMP is much better than MEA; the value is 0.777 moles for AMP as compared to MEA value 0.478 moles. The regeneration efficiency of AMP ranging from 96.39 to 97.26% is superior over MEA which is in the range of (79.91–81.55) %. The entire experimental absorption rate data are plotted with the response surface methodology (RSM) fitted data which shows a good agreement with the experimental value for both the amine solvents.